2012
DOI: 10.1364/josaa.29.000251
|View full text |Cite
|
Sign up to set email alerts
|

Study on the propagation parameters of Bessel–Gaussian beams carrying optical vortices through atmospheric turbulence

Abstract: Based on the integral representation of Bessel function and the extended Huygens-Fresnel principle, an integral expression of the Wigner distribution function (WDF) for partially coherent Bessel-Gaussian beams (PBGBs) propagating through turbulent atmosphere has been obtained. Also, the analytical formulas of the M2-factor for PBGB propagation in such a medium have been derived, which can be applied to cases of different spatial power spectra of the refractive index fluctuations. The performed numerical result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…The investigation results show, in the same condition, the variance of fluctuations of the Bessel beam are smaller than that of the Laguerre Gaussian beam with the same topological charge. Compared with the conventional OAM beams, the Bessel beams show advantages in non-diffraction and self-healing, which can benefit the beam propagation in turbulent atmosphere 24 25 26 . For the coherent and partially coherent Bessel beams propagating through turbulent atmosphere, the statistical properties such as variance of fluctuations of the OAM 24 , M 2 –factor 25 and the variance of the displacement 26 are theoretical studied.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The investigation results show, in the same condition, the variance of fluctuations of the Bessel beam are smaller than that of the Laguerre Gaussian beam with the same topological charge. Compared with the conventional OAM beams, the Bessel beams show advantages in non-diffraction and self-healing, which can benefit the beam propagation in turbulent atmosphere 24 25 26 . For the coherent and partially coherent Bessel beams propagating through turbulent atmosphere, the statistical properties such as variance of fluctuations of the OAM 24 , M 2 –factor 25 and the variance of the displacement 26 are theoretical studied.…”
mentioning
confidence: 99%
“…Compared with the conventional OAM beams, the Bessel beams show advantages in non-diffraction and self-healing, which can benefit the beam propagation in turbulent atmosphere 24 25 26 . For the coherent and partially coherent Bessel beams propagating through turbulent atmosphere, the statistical properties such as variance of fluctuations of the OAM 24 , M 2 –factor 25 and the variance of the displacement 26 are theoretical studied. The results show the Bessel-Gaussian beams are less affected by the turbulent atmosphere with larger values of topological charges 24 25 26 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation on the shape of the beam has been of increasing interest because of the evidence that other types of incidence may be less influenced by turbulence. A wide variety of beam shapes have been considered, including Gaussian [11], Hermite-Gaussian [7], Hermite-cosh-Gaussian [12], cosh (cos)-Gaussian [13,14], Bessel [15,16], annular [14], dark hollow [17,18], Laguerre-Gaussian [19], and flat-topped beams [20][21][22][23][24][25]. Specifically, in recent years, some new attempts have been focused on flat-topped beams, which can be applied in inertial confinement fusion and material thermal processing for laser beams.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of BGBs in turbulent atmosphere have been studied [20][21][22], and it was both theoretically and experimentally demonstrated that spatially partially coherent beams are less affected by turbulence than fully coherent ones [23][24][25][26]. However, as far as we know, the coherence properties of partially coherent BGBs in non-Kolmogorov turbulence have not been examined until now.…”
Section: Introductionmentioning
confidence: 99%